Chiral Mn(III) salen complex immobilized onto ionic liquid modified mesoporous silica for oxidative kinetic resolution of secondary alcohols - Sahoo, Suman; Kumar, Pradeep; Lefebvre, F.; Halligudi, Shivaraj B. (Tetrahedron Letters, 2008)
A supported ionic liquid strategy has been applied for the immobilization of a chiral Mn(III) salen complex onto ionic liquid modified mesoporous silica SBA-15. The immobilized catalyst demonstrated high enantioselectivity and activity in the oxidative kinetic resolution of secondary alcohols, and could be recycled five times without obvious loss of activity. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Mesoporous silica SBA-15; Mn(III) salen; Oxidative kinetic resolution; Secondary alcohol; Supported ionic liquid

Enantioselective hydrogenation of olefins by chiral iridium phosphorothioite complex covalently anchored on mesoporous silica - Sahoo, Suman; Kumar, Pradeep; Lefebvre, F.; Halligudi, Shivaraj B. (Journal of Catalysis, 2008)
Chiral monodentate phosphorous-based ligands have proven effective for the enantioselective hydrogenation of olefins. Binol-derived monodentate phosphorothioite (PS) ligand was synthesized from binol and thiopropyltriethoxysilane, and its iridium complex was covalently anchored to mesoporous silica supports like SBA-15, MCM-41, and MCM-48. These catalysts were characterized by different physicochemical techniques and assessed for their catalytic performances in the heterogeneous asymmetric hydrogenation of itaconic acid and its derivatives. It was found that the catalytic activities and enantioselectivities of the heterogenized iridium complex (IrPSSBA-15) in the hydrogenation reactions were comparable to its homogeneous analogue. Binol-derived monodentate phosphorothioite ligand in heterogeneously anchored form (iridium complex) is a more effective catalyst than the reported monodentate phosphorous ligand systems in the hydrogenation reactions, possibly due to the changes in electronic properties around the iridium metal center. The effects of substrate-to-catalyst molar ratio, solvents, and temperature on substrate conversions and enantioselectivities, of the products were investigated in hydrogenation reactions. (c) 2007 Elsevier Inc. All rights reserved.
Keywords: binol; Enantioselective hydrogenation; Immobilization; iridium complex; itaconic acid; Mesoporous silica SBA-15; monodentate ligand; phosphorothioite ligand

Heteropoly acid-based supported ionic liquid-phase catalyst for the selective oxidation of alcohols - Bordoloi, Ankur; Sahoo, Suman; Lefebvre, F.; Halligudi, Shivaraj B. (Journal of Catalysis, 2008)
A supported ionic liquid strategy has been applied for the immobilization of a heteropolyacid, molybdovanadophosphoric acid, onto ionic liquid-modified mesoporous silica SBA-15. The immobilized catalyst demonstrated high activity in the aerobic oxidation of primary and secondary alcohols to aldehydes and ketones, respectively. No overoxidation of the primary alcohols to carboxylic acids was observed. Secondary alcohols were chemoselectively oxidized to ketones in the presence of primary alcohol, hetero atom, and allyl groups. This catalyst could be recycled five times without obvious loss of activity. (C) 2008 Elsevier Inc. All rights reserved.
Keywords: Air as an oxidant; Mesoporous silica SBA-15; Molybdovanadophosphoric acid; Selective oxidation; Supported ionic liquid

Highly selective catalytic hydrogenation of arenes using rhodium nanoparticles supported on multiwalled carbon nanotubes - Kakade, Bhalchandra A.; Sahoo, Suman; Halligudi, Shivappa B.; Pillai, Vijayamohanan K. (Journal of Physical Chemistry C, 2008)
Rhodium nanoparticles (RhNPs; 4.9 +/- 0.4 nm) supported on multiwalled carbon nanotubes (Rh/MWNT), prepared by simple microwave treatment, show a remarkable catalytic activity for arene hydrogenation with enhanced turnover numbers of similar to 10000; disubstituted arenes show selective conversion of thermodynamically less favorable cis products (>80%). A series of arenes have been tested using various Rh-based catalysts, and a comparison of the results with that of reported rhodium catalysts shows unique selectivity under mild conditions.

MoO3/SiO2: an efficient and selective catalyst for the synthesis 1,3-dioxolane and 1,3-dioxane - Amrute, Amol P.; Sahoo, Suman; Bordoloi, Ankur; Hwang, Young Kyu; Hwang, Jin-Soo; Halligudi, Shiva B. (Catalysis Communications, 2009)
A series of MoO3/SiO2 catalysts with varying amounts of MoO3 has been synthesized and the catalytic activities of these were compared with the known solid acid catalysts in the synthesis of 1,3-dioxolane. MoO3/SiO2 catalyst showed a better activity and selectivity in 1,3-dioxolane synthesis compared to the other catalysts. MoO3/SiO2 catalyst system was further successfully applied for the synthesis of 1,3-dioxanes in the Prins cyclization of olefins and formaldehyde. The proposed catalyst was thermally stable and could be recovered and reused at least in four consecutive cycles with no significant loss in the substrates conversions and products selectivities. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: 1; 3-Dioxolanes; Cycloaddition; MoO3/SiO2; Prins cyclization; Sol-gel method; solid acid catalysts

Oxidative kinetic resolution of alcohols using chiral Mn-salen complex immobilized onto ionic liquid modified silica - Sahoo, Suman; Kumar, Pradeep; Lefebvre, F.; Halligudi, Shivaraj B. (Applied Catalysis A-General, 2009)
The supported ionic liquid strategy has been applied for the immobilization of chiral Mn(III) salen complex onto ionic liquid modified silica. Chiral Mn(III) salen complex was immobilized over silica through a thin film of covalently anchored imidazolium ionic liquid. These catalysts were characterized by N(2) sorption, XRD, MR, DRUV-vis, and elemental analysis. The results showed that the chiral Mn(III) salen complex could be successfully immobilized onto the modified mesoporous materials and that the long-range mesoporous ordering of parent supports was maintained after the immobilization. The immobilized catalyst provided good enantioselectivity and activity in the heterogeneous catalysis of the oxidative kinetic resolution of secondary alcohol and can be recovered and recycled for four times without obvious loss of enantioselectivity and activity. Oxidative kinetic resolutions of meso-diols, hydroxyl ester and primary alcohol were also studied using this catalyst system. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Mesoporous silica; Mn(III) salen; Oxidative kinetic resolution; Secondary alcohol; Supported ionic liquid

Synthesis of chiral sulfoxides by enantioselective sulfide oxidation and subsequent oxidative kinetic resolution using immobilized Ti-binol complex - Sahoo, Suman; Kumar, Pradeep; Lefebvre, F.; Halligudi, Shivaraj B. (Journal of Catalysis, 2009)
Chiral Ti-binol complex was immobilized onto ionic liquid modified SBA-15 and characterized by different physicochemical techniques. The catalyst was found to be highly enantioselective in the heterogeneous asymmetric oxidation of prochiral sulfides to sulfoxides and subsequent oxidative kinetic resolution of the sulfoxides using aqueous tert-butylhydroperoxide as the oxidant. A positive non-linear effect was observed in the oxidation-kinetic resolution of thioanisole using this supported catalyst. The supported catalyst was reused in multiple catalytic runs without any loss of enantioselectivity. (C) 2008 Elsevier Inc. All rights reserved.
Keywords: Kinetic resolution; Mesoporous silica; Non-linear effect; Sulfides; Sulfoxides; Supported ionic liquid; Ti-binol

Ordered mesoporous silica as supports in the heterogeneous asymmetric catalysis - Sahoo, Suman; Bordoloi, Ankur; Halligudi, Shivaraj B. (Catalysis Surveys from Asia, 2011)
Enantioselective synthesis of organic compounds has been studied by homogeneous catalysts for several years. However, these catalysts have yet to make a significant impact on industrial scales for fine chemical synthesis. A primary reason is the designing of a homogeneous asymmetric catalyst, which requires relatively bulky ligands and catalyst recovery and recycling often causes problems. One of the convincing ways to overcome this problem is to immobilise the asymmetric catalyst onto a solid support and the resulting heterogeneous asymmetric catalyst system can, in principle, be readily re-used. A large number of supports such as inorganic oxides including zeolites, alumina, zirconia, silica and organic polymers have been employed as supports in heterogeneous asymmetric catalysis. Therefore, in this review article we have summarized the work done by us in our laboratory on the immobilization of chiral transition metal complexes such as Ru, Ir, Mn and Ti onto ordered mesoporous silica and its asymmetric catalysis. All these immobilized catalysts were well characterized by different physicochemical techniques to confirm the structural retention of the support as well as the active metal complex after immobilization. This report includes our asymmetric catalytic investigations in enantioselective reactions such as hydrogenation of ketones, olefins, oxidation of sulfides and oxidative kinetic resolution of alcohols and sulfoxides through immobilized heterogeneous catalyst systems.
Keywords: Enantioselective hydrogenation; Enantioselective oxidation; Immobilization; Mesoporous silica; Oxidative kinetic resolution

Electrochemically enabled (3+2) cycloaddition of unbiased alkenes and β-dicarbonyls - Suryawanshi, Sharad M.; Sahoo, Suman; Shaligram, Parth S.; Manna, Narugopal; Samanta, Ramesh C. (Chemical Communications, 2024)
A (3+2) cycloaddition between unbiased alkenes and 1,3-dicarbonyls is accomplished by judicious choice of electrode material and electrocatalyst to access dihydrofuran derivatives. A fluorinated porous carbon electrode with appropriate thickness governs unprecedented reactivity. This methodology eliminates the necessity for any stabilizing group within the alkene substrate. This is a rare example of the annulation of unbiased internal and terminal alkenes with cyclic and acyclic beta-dicarbonyls.
Keywords: 1; 3-DICARBONYL COMPOUNDS; DIHYDROFURANS; FACILE SYNTHESIS